Projeto preliminar de transportador helicoidal aplicado à indústria salineira de Mossoró e região - Gualberto, Victor Soares (Universidade Federal Rural do Semi-Árido, 2019)
The industrials conveyors are machines of high importance for an industry productive process. The product locomotion has great influence in final product confection. In the case of this work, the product is refines salt. It is made in high scales in the region of Mossoro and Areia Branca. Due that, on this region are great utilization of conveyors in salt production process. As most machines are made with metals, the producers suffer with corrosion process. In base of it, this work take a suggestion of a helical conveyor made with corrosion material resistant as stainless steel and polymers.
Monografia
Keywords: Transportadores industriais; Sal refinado; Transportador helicoidal; Industrial conveyors; Refined salt; Helical conveyor; ENGENHARIAS::ENGENHARIA MECANICA